Composition of essential oils from Monarda fistulosa L affected by the fungal pathogen Golovinomyces biocellatus (Erysiphales). (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The composition of essential oils from Monarda fistulosa has been studied in healthy plants and in plants affected by the fungal pathogen, Golovinomyces biocellatus (Erysiphales). 35 terpene combinations have been identified. The contents of carvacroland thymol in healthy plants are 45% and 2% respectively. In plants damaged by Golovinomyces biocellatus, the content of carvacrol decreases to 4% and quantity of thymol increases up to 62%.
Keywords: fungal pathogen, Monarda fistulosa, terpenes, thymol, carvacrol, essential oil, mildew.